Theoretical and Experimental Estimation of Uncertainty of Measurement during Calibration of CMM - Dev, Atul; Parkash, Ved; Tandon, Smriti (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948581);" role="presentation">In the present paper we briefly discuss the universal (theoretical) and experimental methods of estimation of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919955);" role="presentation">uncertainty of measurement. <span dir="ltr" style="left: calc(var(–scale-factor)*195.74px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951093);" role="presentation">As an application we have taken the case of manual 3D co-<span dir="ltr" style="left: calc(var(–scale-factor)*445.42px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914363);" role="presentation">ordinate measuring <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*348.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936384);" role="presentation">machine of with 1 <span dir="ltr" style="left: calc(var(–scale-factor)*153.14px); top: calc(var(–scale-factor)*348.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901138);" role="presentation">m least count and this <span dir="ltr" style="left: calc(var(–scale-factor)*243.29px); top: calc(var(–scale-factor)*348.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908146);" role="presentation">machine has been calibrated with the help of a <span dir="ltr" style="left: calc(var(–scale-factor)*432.07px); top: calc(var(–scale-factor)*348.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891393);" role="presentation">Step Gauge. The study <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*361.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913739);" role="presentation">concludes that both universal and experimental methods give fairly identical results and hence universal method <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*374.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956785);" role="presentation">can be used easily for the uncertainty calculation of such machines. <span dir="ltr" style="left: calc(var(–scale-factor)*361.51px); top: calc(var(–scale-factor)*374.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946227);" role="presentation">This <span dir="ltr" style="left: calc(var(–scale-factor)*383.35px); top: calc(var(–scale-factor)*374.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03205);" role="presentation">is first of its kind of work where <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*388.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908674);" role="presentation">theoretically estimated uncertainty value has been compared w.r.t. the practically observed value.